أثر المناخ على راحة الإنسان في منطقة الحمدة بالجبل الأخضر - ساسيحمد محمد احمد (Aljameai, 2022)
الملخص: تناولت هذه الدراسة أثر المناخ على راحة الإنسان في منطقة الحمدة بالجبل الأخضر, وهدفت إلى معرفة كيف يؤثر المناخ على راحة الإنسان في المنطقة , كما هدفت إلى معرفة الشهور المريحة وغير المريحة للإنسان في المنطقة , ولتحقيق هذه الأهداف تم استخدام المنهج الوصفي وكذلك المنهج الكمي وذلك باستخدام دليل الحرارة والرطوبةTHI ) ), كما تم جمع البيانات المناخية اللازمة من مصادر مختلفة , وقد توصلت هذه الدراسة إلى وجود اشهر مريحة واشهر غير مريحة للإنسان في منطقة الحمدة , حيث أن اشهر ابريل و مايو ويونيو وأكتوبر ونوفمبر مريحة للإنسان في منطقة الحمدة , وان اشهر يناير وفبراير ومارس وديسمبر غير مريحة بسبب برودتها, وتوصي الدراسة بإقامة محطة أرصاد جوية شاملة في منطقة الحمدة لأجل دراسة جميع عناصر المناخ في المنطقة , كما توصي الدراسة بحماية الغطاء النباتي الطبيعي المحيط بالمنطقة لما له من أهمية كبيرة في الحفاظ على البيئة والمناخ . Abstract : This study examined the effect of climate on human comfort in the area of EL Hemeda, The study aimed to know how the climate affects human comfort in the region of EL Hemeda , as it aimed to know the comfortabl and uncomfortable months of a person in the region,To achieve these goals, the descriptive approach was used as well as the quantitative approach by applying the temperature and humidity index and this determine the comfortable and uncomfortable months in the area of EL Hemeda , the necessary climate data were also collected from various sources,The study found that the comfortable months in the EL Hemeda region are April May June October and November and that the uncomfortable months are January February March and December due their coldness,The study recommends the establishment of a comprehensive meteorological station in the area of EL Hemeda, It also recommends maintaining the vegetation surrounding the area because of great importance to the environment and climate.